THE USE OF SOCIAL DEIXIS IN ALEXANDRE DUMAS’ THE COUNT OF MONTE CRISTO - Leonardo Berliantoro; Yuli Widiana; Obat Mikael Depari (Humaniora Scientia, 2017)
This study discusses the use of social deixis. It focuses on the kinds and the usage of socialdeixis. This research is descriptive in nature. It was conducted through the following steps:collecting, arranging, classifying, and analyzing the data. The data were obtained from a novelwritten by Alexandre Dumas’ entitled The Count of Monte Cristo. The unit of analysis of thisresearch is all of sentences containing socialdeixis. To get the sample, this research applied totalsampling. Consequently, all of the data were analyzed one by one. To find out the kinds of socialdeixis, referential method was used. Likewise, to search the aims of usage, pragmatic equivalentmethod was applied. The data analysis shows that based on its kinds, social deixis found in thenovel includes relational social deixis (10 items) and absolute social deixis (20 items). Amongthem, absolute social deixis is more frequently used than relational social deixis. While, due to itsaims of usage, social deixis is applied to express politeness and respect (10 items), intimacy (5items), and identify authority (21 items). In this case, social deixis is mostly used to identifyauthority.